Consistency and Coherence of Turtle Conservation Policies in Venu Island Wildlife Sanctuary, Kaimana, West Papua - Zeth Parinding; Sambas Basuni; Herry Purnomo; Nandy Kosmaryandi; Yusli Wardiatno (Institut Pertanian Bogor (IPB University), 2016)
Policy management of turtle conservation in the region of Venu Island Wildlife Sanctuary, Kaimana, West Papua is indispensable. Therefore, this study aimed at examining the turtle conservation policy and it’s implementation, both the consistency and coherence. The analytical method used is content analysis and simple mathematic statistics. The consistency of turtle conservation management policies is found inconsistent in implementation. Similarly, coherence between the policy on turtle conservation management with government policy is found incoherent, as it is more oriented to